2003
DOI: 10.1183/09031936.03.00040803
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroids and survival in chronic obstructive pulmonary disease: does the dose matter?

Abstract: Recent data suggest that inhaled corticosteroids reduce the number of clinical exacerbations in chronic obstructive pulmonary disease (COPD). It remains unknown whether a dose/response relationship exists. The present study was conducted to evaluate the long-term impact of varying doses of inhaled corticosteroids on COPD mortality.Hospital discharge data were used to identify all patients aged o65 yrs recently hospitalised due to COPD in Alberta, Canada (n=6,740). The relative risk (RR) for allcause mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
1
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 44 publications
0
52
1
2
Order By: Relevance
“…reduction of ≥0. The total number of COPD exacerbations requiring Improvements in the SGRQ total scores were hospitalization was very low in all treatment groups significantly greater (p ≤ 0.035) in both budesonide/ (range [11][12][13][14][15][16][17][18][19][20][21][22]; the number of events per patientformoterol groups compared with the budesonide, treatment year was significantly different for formoterol and placebo groups (table V). These budesonide/formoterol 320/9 μg (0.158) compared improvements were clinically meaningful (i.e.…”
Section: Secondary Efficacy Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…reduction of ≥0. The total number of COPD exacerbations requiring Improvements in the SGRQ total scores were hospitalization was very low in all treatment groups significantly greater (p ≤ 0.035) in both budesonide/ (range [11][12][13][14][15][16][17][18][19][20][21][22]; the number of events per patientformoterol groups compared with the budesonide, treatment year was significantly different for formoterol and placebo groups (table V). These budesonide/formoterol 320/9 μg (0.158) compared improvements were clinically meaningful (i.e.…”
Section: Secondary Efficacy Variablesmentioning
confidence: 99%
“…This result was driven by the exacerbations requiring treatment with oral corticosteroids (79-120 events). The number of exacerbations resulting in hospitalization was very low across treatment groups (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22); the number per patient-treatment year was significantly different for budesonide/formoterol 320/9 μg (0.158) versus other treatment groups (0.081-0.108) except budesonide/formoterol 160/9 μg (0.139), and for budesonide/formoterol 160/9 μg versus formoterol (0.081) [p ≤ 0.05]. All treatments were generally well tolerated.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Results of long-term observational studies with respect to exacerbations and mortality are mixed. [48][49][50][51][52][53] The COPE study, a double-blind discontinuation study of fl uticasone (1,000 μg/d), reported that patients who discontinued inhaled corticosteroid therapy had a signifi cantly higher recurrence risk of exacerbations than patients who remained on fl uticasone treatment. 49 We note several limitations in this literature and our work.…”
Section: Inhaled Corticosteroids and Copdmentioning
confidence: 99%
“…Die Exazerbationsrate verminderte sich jedoch im Verhältnis zu Ausmaû der eingeschränkten Lungenfunktion [42]. Retrospektive, epidemiologische Untersuchungen legten eine Verminderung der Mortalität bei Patienten nahe, die wegen einer Exazerbation stationär behandelt wurden [43]. Es wurde jedoch überzeugend belegt, dass diese erwartungsvolle Aussage auf einer fälschlichen Zuordnung der Dauer der inhalativen Steroidtherapie beruhte [44,45].…”
Section: Antiinflammatorische Therapie Der Copdunclassified